Pengaruh Good Governance terhadap Kemiskinan di Negara Berkembang - Rio Anugerah Utama; Joan Marta (Universitas Negeri Padang, 2025)
This study examines the impact of good governance on poverty levels in developing countries. Good governance is measured using five World Bank indicators: Control of Corruption, Government Effectiveness, Regulatory Quality, Political Stability and Absence of Violence/Terrorism, and Voice and Accountability. The analysis employs panel data regression from 16 developing countries over the period 2008–2022, using a quantitative approach through the Random Effect Model (REM). The findings indicate that both individually and jointly, good governance indicators have a significant effect on poverty. Control variables, namely Gross Domestic Product (GDP) per capita and Labor Force Participation Rate (LFPR), also play an important role. These results highlight that improving governance quality through transparency, policy effectiveness, and public participation is a strategic effort to sustainably alleviate poverty in developing countries.